Continuing the continuous harvests of food production: from the perspective of the interrelationships among cultivated land quantity, quality, and grain yield - Peng Cheng; Yang Zhang; Ke Liu; Xuesong Kong; Shiman Wu; Huafei Yan; Ping Jiang (Humanities & Social Sciences Communications)
Abstract The rapid population growth around the world has become one of the main challenges for countries to ensure adequate food supply. To address this difficulty and ensure adequate food production, sustainable land use, in particular sustainable cultivated land (CL) use, can make a great contribution. Sustainable utilization of CL encompasses several aspects such as quantity and quality, but previous studies have focused on increasing food production, while the interrelationships among cultivated land quantity, quality, and grain yield (CLQQGY) have still received less attention. Hence, based on the GlobeLand30 data during 2000–2020, this paper analyzed the changes of CLQQGY in 130 prefecture-level cities in the Yangtze River Economic Belt (YREB) in China and explored whether the current consecutive harvests is sustainable in the future to feed increasing population. The results revealed the areal loss and quality degradation of CL in most cities in the YREB, the total CL area decreased by 31.07 × 104 hm2 and 282.59 × 104 hm2 during 2000–2010 and 2010–2020, respectively, and the CL quality declining trend was presented in 68.46% and 69.23% cities in the YREB during 2000–2010 and 2010–2020, respectively. Even with such acreage and ecological losses, the total grain yield still increased by 3.77% and 9.53% during 2000–2010 and 2010–2020, respectively, continuing the miracle “continuous harvests” of grain yield in this region. This successive increase in food production in the context of decreasing acreage and ecological deterioration of CL depend mainly on the amount of chemical fertilizer usage, the total power of agricultural machinery and rural electricity consumption. However, due to the heavy reliance on a growth model driven by resource inputs, this type of harvest appeared to be unsustainable because of the significant negative effects brought out by overusing resources. With a view to achieving sustainable use of CL and food production, therefore, this paper proposed policies to promote the sustainable use of CL and food supply for supporting the survival of increasing population through the full implementation of administrative regulations and economic measures that focus on the balance among the quantity and quality and food production of CL in the process of agricultural production and CL management.